Drug Poisoning Deaths according to Ethnicity in Utah. (11th December 2013) - Merrill, Ray M.; Hedin, Riley J.; Fondario, Anna; Sloan, Arielle A.; Hanson, Carl L.
Abstract : This study characterizes drug-related deaths according to ethnicity in Utah during 2005–2010, based on data from the Utah Violent Death Reporting System (UTVDRS). Hispanics made up 12.1% (12.5% male and 11.7% female) of deaths. The most frequently identified drugs among decedents were opiates, then illicit drugs, benzodiazepines, over-the-counter medication, and antidepressants. Death rates for each drug were significantly greater in non-Hispanics than Hispanics. Most decedents used a combination of drugs. For each combination, rates were significantly greater for non-Hispanics than Hispanics, with an exception for opiates and illicit drugs combined, where there was no significant difference. Approximately 79% of non-Hispanics and 65% of Hispanics had one or more of the selected problems (e.g., mental, physical, or crisis related). Rates for each combination of problems were significantly greater in non-Hispanics, with the exception of crisis. Hispanics were less affected by the rise in prescription drug abuse. Hispanic decedents had a greater proportion of illegal drugs, consistent with it being more difficult to obtain prescription drugs. Hispanic decedents were less likely to have physical and mental health problems, which may be related to a smaller chance of diagnosis of such problems through the healthcare system.